Changes in Etiology of Invasive Bacterial Infections in Infants Under 3 Months of Age in Korea, 2006–2020. Issue 12 (20th September 2022) - Song, Seung Ha; Lee, Hoan Jong; Song, Eun Song; Ahn, Jong Gyun; Park, Su Eun; Lee, Taekjin; Cho, Hye-Kyung; Lee, Jina; Kim, Yae-Jean; Jo, Dae Sun; Kim, Jong-Hyun; Kang, Hyun Mi; et al.
Abstract : Objectives: Invasive bacterial infection (IBI) causes a significant burden in infants. In this study, we analyzed changes in epidemiology of IBI among infants in Korea. Methods: A retrospective multicenter-based surveillance for IBIs in infants <3 months of age was performed during 2006–2020. Cases were classified as an early-onset disease (EOD) (0–6 days) or late-onset disease (LOD) (7–89 days). The temporal trend change in proportion of pathogens was analyzed. Results: Among 1545 cases, the median age was 28 days (IQR: 12, 53) and EOD accounted for 17.7%. Among pathogens, S. agalactiae (40.4%), E. coli (38.5%), and S. aureus (17.8%) were the most common and attributed for 96.7%. Among EOD (n = 274), S. agalactiae (45.6%), S. aureus (31.4%), E. coli (17.2%) and L. monocytogenes (2.9%) were most common. Among LOD (n = 1274), E. coli (43.1%), S. agalactiae (39.3%), S. aureus (14.9%) and S. pneumoniae (1.3%) were most common. In the trend analysis, the proportion of S. aureus (r s = −0.850, P < 0.01) decreased significantly, while that of S. agalactiae increased (r s = 0.781, P < 0.01). Conclusion: During 2006–2020, among IBI in infants <3 months of age, S. agalactiae, E. coli, and S. aureus were most common and an increasing trend of S. agalactiae was observed.